1986
DOI: 10.1099/0022-1317-67-9-2023
|View full text |Cite
|
Sign up to set email alerts
|

Neuritic Transport of Herpes Simplex Virus in Rat Sensory Neurons in vitro. Effects of Substances Interacting with Microtubular Function and Axonal Flow [Nocodazole, Taxol and Erythro-9-3-(2-hydroxynonyl)adenine]

Abstract: SUMMARYHerpes simplex virus type 1 and a fluorescein-labelled lectin (wheat germ agglutinin) were selectively transported to nerve cell bodies located in the inner compartment of a two-chamber tissue culture system after the application of virus or lectin to the neuritic processes in the outer culture compartment. Taxol, which stabilizes and alters intracellular arrangements of microtubules, and nocodazole, which disrupts microtubules, both inhibited this retrograde axonal transport of viral particles and lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 16 publications
(12 reference statements)
3
87
1
Order By: Relevance
“…102,103 The rapid movement of HSV in a retrograde manner would require association with a minusend-directed motor molecule to propel the nucleocapsids toward the minus end of the microtubule network. Ye et al 81 demonstrated that the HSV UL34 protein Reactivation from latency and anterograde transport to the nerve terminal…”
Section: Virus Attachment and Entrymentioning
confidence: 99%
“…102,103 The rapid movement of HSV in a retrograde manner would require association with a minusend-directed motor molecule to propel the nucleocapsids toward the minus end of the microtubule network. Ye et al 81 demonstrated that the HSV UL34 protein Reactivation from latency and anterograde transport to the nerve terminal…”
Section: Virus Attachment and Entrymentioning
confidence: 99%
“…Previous studies in which microtubule-depolymerizing drugs were used to inhibit transport of HSV did not assess the metabolic activity of the drug-exposed neurons (Kristensson et al, 197 1;Openshaw et al, 1978;Kristensson et al, 1986;Bosem et al, 1990). Therefore, it is impossible to know whether transport was inhibited due to the loss of microtubules or more severe cell destruction.…”
Section: Autoradrographymentioning
confidence: 99%
“…Previous studies indicate that HSV takes advantage of the host neuron's natural machinery for retrograde axonal transport, using microtubules for translocation from the nerve terminals in the periphery to the cell bodies of dorsal root ganglion neurons in rive (Kristensson et al,197 1). Microtubules and translocator molecules have also been implicated in the transport of HSV from the neurites to the cell bodies of dorsal root ganglion cells in vitro (Kristensson et al, 1986). However, no study has yet provided quantitative evidence of the dependence of HSV transport on intact microtubules in metabolically active neurons.…”
mentioning
confidence: 99%
“…Rabies virus infects a great variety of neuronal cell lines (Clark, 1978;Honda et al, 1984;Iwasaki & Clark, 1977;Tsiang et al, 1983a) as well as primary dissociated neuron cultures (Lycke & Tsiang, 1987;Tsiang et al, 1983aTsiang et al, , b, 1986. Whereas conventional neuronal cultures are less appropriate for the investigation of viral transport, neurons cultivated in a compartmentalized culture system as described by Campenot (1977) will demonstrate convincingly the transport of herpes simplex virus in vitro (Kristensson et al, 1986;Lycke et al, 1984;Ziegler & Herman, 1980) and the retrograde transport of both fixed and street rabies viruses in cultured rat sensory neurons (Lycke & Tsiang, 1987;Tsiang, 1988). In this system, herpes and rabies viruses were transported in a retrograde fashion with a velocity in the range of 50 mm/day (herpes virus) and 25 mm/day (rabies virus) (Lycke et al, 1984;Lycke & Tsiang, 1987).…”
Section: Introductionmentioning
confidence: 99%